A morphological survey of Ustilago trichophora, a smut fungi and evaluation as bioherbicidal agent for barnyard grass (Echinochloa crus-galli) - Tóth, Tamás; Kövics, György (Acta Agraria Debreceniensis, 2016)
Ustilago trichophora (Link) Kunze is a widespread smut fungus in all over the world. This fungus is pathogenic on species of Echinochloa genus. The subject of present research was that smut fungi occurrence on barnyard grass (Echinochloa crus-galli). Numerous barnyard grass plants with symptoms of smut galls caused by Ustilago trichophora on stems were collected from two counties, víz. Hajdú-Bihar (East-Hungary) and Jász-Nagykun-Szolnok (Middle-Hungary). The infested plants were examined in laboratory, which included the observation of the symptoms and the morphological properties of the spores and the colonies developed from sporidia. The results suggested that this fungus could be effective against barnyard grass weed so the biological control of this weed plant (Echinochloa cruss-galli) can be managed by using Ustilago trichophora biopreparates. As Ustilago trichophora can produce abundant sporidia in liquid culture, a high effectiveness control should be apply by Ustilago trichophora smut fungus as a mycoherbicide in Echinochloa weed control.